2020
DOI: 10.1200/jco.19.01706
|View full text |Cite
|
Sign up to set email alerts
|

Superior Intellectual Outcomes After Proton Radiotherapy Compared With Photon Radiotherapy for Pediatric Medulloblastoma

Abstract: PURPOSE Proton radiotherapy (PRT) may lessen the neuropsychological risk traditionally associated with cranial radiotherapy for the treatment of pediatric brain tumors by reducing the dose to normal tissue compared with that of photon radiotherapy (XRT). We examined the change in intellectual scores over time in patients with pediatric medulloblastoma treated with craniospinal PRT versus XRT. METHODS Intelligence test scores were obtained for a sample of pediatric patients treated between 2007 and 2018 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 25 publications
5
181
1
1
Order By: Relevance
“…The uniform target dose can be achieved using the passive-scattering proton therapy (PSPT) technique or the more advanced intensity-modulated proton therapy (IMPT) technique employing scanned beams. Importantly, some clinical trials have indicated the advantages of proton therapy over traditional photon-based therapy [3][4][5][6] . However, there are still many challenging issues in modern proton therapy.…”
mentioning
confidence: 99%
“…The uniform target dose can be achieved using the passive-scattering proton therapy (PSPT) technique or the more advanced intensity-modulated proton therapy (IMPT) technique employing scanned beams. Importantly, some clinical trials have indicated the advantages of proton therapy over traditional photon-based therapy [3][4][5][6] . However, there are still many challenging issues in modern proton therapy.…”
mentioning
confidence: 99%
“…74 Recently, a prospective, multi-centre, high-quality database-derived study was published which for the first time compared intellectual trajectories between paediatric patients treated with PBT versus those treated with photon RT and demonstrated a translation of theoretical dosimetric advantages into clinically measurable outcomes. 75 Randomised controlled trials are challenging to perform when testing new radiotherapy technologies. 1,73 This has been recognised by the Trans Tasman Radiation Oncology Group (TROG), and the Assessment of New Radiation Oncology Technologies and Treatment (ANROTAT) Project was developed to address these complexities.…”
Section: What Evidence Is Needed?mentioning
confidence: 99%
“…Meanwhile, 104 particle therapy facilities are in clinical operation worldwide 2 . For protons, reduced neurotoxic effect compared to photons was demonstrated by the studies of Kahalley et al [25,26]. Pediatric patients treated for brain tumors with protons showed less neuropsychological impairments in terms of intelligence, perceptual reasoning, processing speed, and working memory than those treated with X-rays [25,26].…”
Section: Neurotoxic Effects Of Ionizing Radiation On the Human Brainmentioning
confidence: 99%